Bioanalytical chemistry - Manz, Andreas Pamme, Nicole Lossifidis, Dimitri (Imperial College Press, 2004)
Interdisciplinary knowledge is becoming more and more important to themodern scientist. This invaluable textbook covers bioanalyticalchemistry (mainly the analysis of proteins and DNA) and explainseverything for the nonbiologist. Electrophoresis, mass spectrometry, biosensors, bioassays, DNA and protein sequencing are not necessarilyall included in conventional analytical chemistry textbooks. The bookdescribes the basic principles and the applications of instrumentaland molecular methods. It is particularly useful to chemistry andengineering students who already have some basic knowledge abouta.